Between Crisis and Convention: How Should We Address Contingency? - Bibler, Trevor (The Hastings Center report, 2020)
The Covid-19 pandemic has brought about renewed conversation about equality and equity in the distribution of medical resources. Much of the recent conversation has focused on creating and implementing policies in times of crisis when resources are exhausted. Depending on how the pandemic develops, some communities may implement crisis measures, but many health care facilities are currently experiencing shortages of staff and materials even if the facilities have not implemented crisis standards. There is a need for shared conversation about equality and equity in these times of contingency between conventional and crisis medicine. To respond well to these challenges, I recommend that institutions rely on policy, professional education, and ethics consultation. As is the case with crisis policies, creating contingency policies requires that health care professionals decide on how, specifically, to achieve equity. A policy is only as effective as its implementation; therefore, institutions should invest in context-specific education on contingency policies. Finally, ethics consultation should be available for questions that contingency policies cannot address.